Ecological homelands: towards a counter-ontopology of landscape design. (17th February 2020) - Abbott, Mick; Boyle, Cameron
ABSTRACT: Geographer John Wylie critiques problematic claims of belonging to place that would suggest a natural connection between people and topos. Such ontopological beliefs in a homeland rely on environmental determinism or historicization to assert an inextricable link between blood and soil formed over centuries of human occupation and use. In this article we examine ways ontopology operates in the protected areas of Aotearoa New Zealand, which as places that are understood as 'wild' and thus outside of the presence of people, provide an intriguing contrast for considering ontopology and how it may be approached through design. Wylie identifies two counter-ontopological positions for landscape: one an orientation towards hospitality, welcome, and sanctuary; the other seeking to destabilise homeland thinking through unsettling, dislocating, and distancing such troubling claims of belonging to place. Drawing on these directions, we examine a landscape design project undertaken by Lincoln University's Landscope Designlab at Ararira Wetland in the South Island of Aotearoa New Zealand, which reimagines protected areas by expanding ways people might engage with them through the design of counter-ontopological forms.